Computerized neuropsychological assessment in post-COVID condition - Cristina Delgado-Alonso; Jordi A. Matias-Guiu; Jesús M. Alvarado; Maria Diez-Cirarda; Silvia Oliver-Mas; Esther Valiente-Gordillo; María José Gil-Moreno; José-Manuel Alcalá Ramírez del Puerto; Jorge Matías-Guiu; Alfonso Delgado-Álvarez (PLoS ONE, 2025)
Background Attention/ processing speed deficits with or without executive function and episodic memory deficits have been suggested as a relatively characteristic cognitive profile of people with post-COVID condition (PCC). Most studies have been performed using standardized paper and pencil neuropsychological assessment. Sensitive and applicable tests are needed to improve the diagnostic capacity of patients with PCC. Objectives In this study, we aimed to investigate the dimensions of a comprehensive computerized neuropsychological battery and to characterize the cognitive characteristics of patients with PCC. Materials and methods Five hundred and eight participants were enrolled in the study (PCC = 227, Healthy Controls, HC = 281) and underwent cognitive assessment focused on attention, concentration, executive functions, and episodic memory. We conducted a multi-group confirmatory factor analysis. Factor scores were obtained to compare the PCC and HC groups and partial invariance analysis was performed to identify relevant cognitive processes that differentiate the two groups. Results The proposed four-factor model showed adequate fit indices. There were differences in attention, concentration, and executive functions factor scores with small to moderate effect sizes and with a particular implication of attention processes based on measurement invariance analysis. Impairments in reaction times and divided attention were especially relevant in patients with PCC. Conclusions The battery revealed four factors representing attention, concentration, executive functions, and episodic memory. The PCC group performed worse than the HC group in attention, concentration, and executive functions. These findings suggest the validity of computerized neuropsychological assessment, which could be particularly useful in PCC.